THE APPLICATION OF INNOVATIVE TECHNOLOGIES AND PEDAGOGICAL TECHNOLOGIES IN MATHEMATICS LESSONS IN ELEMENTARY SCHOOLS (Web of Teachers: Inderscience Research, 2024)
The primary goal of primary education is to awaken a child's interest in learning, literacy, working with various information, knowledge of basic mathematical operations and their application in everyday life, logical and creative thinking, self-management, self-management in the team, mastering the rules of written and oral communication culture, and the formation of skills such as organizing educational activities.